2015
DOI: 10.1155/2015/968450
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present and Future of Respiratory Research: A Survey of Canadian Health Care Professionals

Abstract: Areas of development, such as research skills, greater funding opportunities and mentorship to increase the research capacity of health care professionals in respiratory health were identified. Health professional researchers have an important role in the national respiratory research strategy to increase interdisciplinary engagement and build collaborative teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…This group felt that lack of mentorship and institutional support were signi cantly more impactful than those that were happy with their current research involvement (Figure 1A). The data agrees with a survey of Canadian respiratory workers, which suggested that lack of mentorship was a more important barrier for those not involved in research when compared to those actively engaged in research (12). Clinicians and non-clinicians ranked barriers to research participation relatively equally (Figure 1A), with more than 85% of participants selecting managing competing activities, lack of time, funding and infrastructure as a barrier.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This group felt that lack of mentorship and institutional support were signi cantly more impactful than those that were happy with their current research involvement (Figure 1A). The data agrees with a survey of Canadian respiratory workers, which suggested that lack of mentorship was a more important barrier for those not involved in research when compared to those actively engaged in research (12). Clinicians and non-clinicians ranked barriers to research participation relatively equally (Figure 1A), with more than 85% of participants selecting managing competing activities, lack of time, funding and infrastructure as a barrier.…”
Section: Discussionsupporting
confidence: 87%
“…Study participants with clinical responsibilities were signi cantly less con dent than non-clinicians in research skills, with the largest disparity being in applying for research funding and publishing results (Figure 1B). Previous studies have also suggested that this lack of con dence could be a barrier to participating in interdisciplinary collaboration, particularly with colleagues who are more research focussed (9,12). Clinicians and non-clinicians generally agreed on the bene ts and barriers to interdisciplinary collaboration (Figure 2A); with 80% identifying schedule incompatibility, lack of funding, identifying interested collaborators and lack of shared infrastructure as a moderate or major barrier.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…One of the main limitations of this study was the answering rate of 45.31%, which, despite matching with the ones found in the literature [18,[44][45][46][47][48], may not be representative of the whole wide world. Another limitation was the physiotherapists' questioning through a multiple choice and not through an open answer questionnaire.…”
Section: Factors That Influence In the Choice Of Therapeutic Techniquesmentioning
confidence: 68%
“…Similarily, Nonoyama [18] used the WReN Spider to measure experience plus interest in up-skilling in each of the Spider limbs in respiratory Health Professionals. The questionnaire consisted of closed ended questions, but open-ended questions were used to collect additional comments.…”
Section: Resultsmentioning
confidence: 99%